Deskripsi Integritas dari Aspek Tanggung Jawab Belajar Siswa dalam Proses Pembelajaran Matematika di Kelas V SDN 39 Pontianak Kota - Ariani, Desi; Bistari, Bistari; Kartono, Kartono (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This Integrity is one of the important values integrated in learning. In the value of integrity, there is an aspect of responsibility that exists in a student. This study describes the learning process carried out by teachers related to the character of responsibility and describes the character of student learning responsibility in grade V SDN 39 Pontianak Kota. Descriptive qualitative is the method in this study. Observation, interviews, questionnaires, and documentatuon were used as data collection techniques. Data analysis using interactive analysis of the Milles and Hurberman model. The data validity check techniques used are credibility, transfermability, dependability, and comfirmability tests. The implementation of learning that is carried out has brought out the character of learning responsibility in it. This can be seen in the lesson plans made by teachers including the value of responsibility, the selection of learning methods supports the cultivation of responsibility, namely by providing assignments and questions, classroom conditioning and classroom management as well as assessment and evaluation of learning related to the character of responsibility carried out by the teacher. The character of student learning responsibility in class V is already available in the learning process but with different levels. This is seen based on indicators of responsibility, namely doing tasks and homework well, being responsible for every action, picketing according to a predetermined schedule, doing group tasks together. A total of 4 people with medium responsibility category, 21 with high responsibility category and 5 people with very high responsibility category.